Synthesis, Characterization and Antimicrobial Activity of Transition Metal Complexes of Schiff Base Ligand Derived from 3-Ethoxy Salicylaldehyde and 2-(2-Aminophenyl) 1-H-benzimidazole - Matangi Sunitha; Pragathi Jogi; Bathini Ushaiah; C. Gyana Kumari (E-Journal of Chemistry)
Metal complexes of Ni(II), Co(II), Cu(II), Mn(II) and Zn(II) VO(IV) with a Schiff base derived from 3-Ethoxy Salicylaldehyde and 2-(2-amino-phenyl)1-H-Benzimidazol(2-[(Z)-{(2-(1H-benzimidazole-2yl)phenyl] imino} methyl]-6-ethoxy phenol-BMEP) were synthesized successfully. The resulting complexes were characterized by elemental analysis, magnetic moment measurements, conductivity measurements, IR, UV-VIS, 1H NMR, mass spectra and ESR spectral studies. According to these data, we propose an octahedral geometry to all the metal complexes. Antimicrobial activity of the ligand and its metal complexes were studied against two gram negative bacteria: E. coli, Pseudomonas flourescence and two gram positive bacteria: Bacillus subitilis, Staphylococcus aureus. The activity data show that the metal complexes are more potent than the free ligand.